2014
DOI: 10.1007/s11136-014-0831-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life profile in Italian long-term cancer survivors

Abstract: Our data support the usefulness of multi-disciplinary follow-ups for long-term cancer survivors and the need to pay particular attention to the psycho-emotional long-term and late-presenting sequels of cancer and its treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 29 publications
11
8
0
1
Order By: Relevance
“…Participants with better education and still working participants have both showed better Physical functioning, less Role limitations (due to physical or emotional problems), less Bodily pain, and better General health with respect to their counterparts. These data are not surprising; they expand and complement what was found in previous studies [1,15,21,22]. For example, in a study involving 24,810 US adults with self-reported physician diagnosis of cancer and 382,837 US adults with no cancer history, Clarke et al [22]showed how the non-working active cancer subsample, compared to those who claimed not to be, more often reported good or excellent health (although in a smaller percentage than the controls without any experience of cancer).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Participants with better education and still working participants have both showed better Physical functioning, less Role limitations (due to physical or emotional problems), less Bodily pain, and better General health with respect to their counterparts. These data are not surprising; they expand and complement what was found in previous studies [1,15,21,22]. For example, in a study involving 24,810 US adults with self-reported physician diagnosis of cancer and 382,837 US adults with no cancer history, Clarke et al [22]showed how the non-working active cancer subsample, compared to those who claimed not to be, more often reported good or excellent health (although in a smaller percentage than the controls without any experience of cancer).…”
Section: Discussionsupporting
confidence: 91%
“…In line with that which has already been described in the literature [1,15,16], there are gender differences. In the present study, women showed worse Physical functioning, more Bodily pain, Vitality, and worse Mental health.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These observations confirm the results of several previously published international studies and support the need for regular psychological/psychiatric evaluation of cancer patients and cancer survivors (13,52,53,54).…”
Section: Figuresupporting
confidence: 90%
“…Research on long-term sequelae of cancer survivors indicates that survivors can reach QoL levels comparable to those of the general population but that specific detriments mainly in the psychosocial domain persist [14][15][16][17][18][19]. Our large population-based study corroborates that overall QoL in long-term cancer survivors on average is comparable to population norms but that deficits in social, role, emotional, cognitive, and physical functioning as well as in specific symptoms and financial difficulties are more prevalent in LTSs.…”
Section: Discussionsupporting
confidence: 76%